Personal VPN Server with Load-Balancing and Obfuscation Method - Bujang, Sandra (Journal of Computing Technologies and Creative Content, 2019)
Personal VPN Server gives users the opportunity to host their own VPN server rather than hosting or subscribing to any existing third-party VPN provider. It provides a cost-effective VPN solution to Internet users with extra security and features that will improve the use of VPN and increase its efficiency Raspberry Pi is used as the main hardware platform where the OpenVPN will be configured as the server. Raspberry Pi also configured will load-balancing and obfuscation features. These help to increase the overall throughput, provide redundancy to the server and preventing the VPN from being detected or blocked while in public network. Overall analysis concluded that the Personal Home VPN Server can be as efficient as commercialized VPNs in the market but with a more reliable cost.